Metode Direct Polymerase Chain Reaction untuk Melacak Campylobacter sp. pada Daging Ayam (DIRECT POLYMERASE CHAIN REACTION METHOD FOR DETECTION CAMPYLOBACTER SP. OF POULTRY MEAT) - ., Andriani; Sudarwanto, Mirnawati; Setiyaningsih, Surachmi; Kusumaningrum, Harsi Dewantari (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
Campylobacter sp. is the most commonly reported as agent of foodborne zoonosis causing acutegastroenteritis in humans. Poultry meat is considered as a major source of C. jejuni infection in human.The conventional methods for detecting foodborne bacteria is time-consuming which rely on the of thebacteria in culture media, followed by biochemical identification. In this study polymerase chain reaction(PCR) technique was used for rapid identification of the pathogenic Campylobacter sp. The samples usedwere 298 chicken carcass with sold in supermarkets and traditional markets, and were carried out inaccordance the isolation protocol ISO/ DIS 10272-1994. Identification was performed using biochemicalAPI Campy. The direct PCR (DPCR) assay with two sets of primers was employed for isolation andidentification of C. jejuni and C. coli. The result of the isolation and identification both by conventional orPCR methods showed that chicken carcasses both from supermarket and traditional market werecontaminated with C. jejuni and or C. coli. Prevalence of Campylobacter sp. contamination in chicken meatwas higher by DPCR (62.6%) than by conventional (19.8%), indicating that DPCR technique was moresensitive than conventional method with detection limit for C. jejuni was103 cfu/ml.
Keywords: direct PCR, Campylobacter jejuni, Campylobacter coli, poultry meat